(untitled) (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: evaluate the shear bond strength of metallic brackets bonded with two adhesive systems to eroded enamel surfaces. Methods: sixty bovine incisors were used and divided into four groups (n = 15). The bonding procedures were performed with metallic brackets and 37% phosphoric acid etching, and divided as follows: Group 1, healthy enamel with Transbond XT adhesive system (3M Unitek, Monrovia, USA); Group 2, eroded enamel with Transbond XT adhesive system; Group 3, healthy enamel with Orthoprimer/Orthobond adhesive system (Dental Morelli Ltda, Sorocaba, Brazil); and Group 4, eroded enamel with Orthoprimer/Orthobond adhesive system. Teeth erosion was performed with Classic CokeTM during 14 days. After 24 h of bonding procedures, specimens were subjected to shear loading using a universal machine for mechanical testing at a crosshead speed of 1 mm/min. Results: the shear bond strength means were: Group 1, 19.04(3.24) MPa; Group 2, 18.6(4.25) MPa; Group 3, 12.76(2.78) MPa; and Group 4, 13.01(3.22) MPa. No statistically significant differences were found between groups 1 and 2, and between groups 3 and 4. Statistically significant differences were found between groups 1 and 3, and between groups 2 and 4. The adhesive remnant index (ARI) scores indicated no significant differences among the tested groups. Conclusions: acid erosion did not change shear bond strength of metallic brackets bonded with both adhesive systems. Transbond XT adhesive system showed higher shear bond strength than Orthoprimer/Orthobond adhesive system.